Pengembangan Desain dan Fungsi Kemasan untuk Criping Pisang “Bu Tini” sebagai Upaya Branding UMKM di Semarang (Lembaga Pengembangan Kinerja Dosen, 2025)
The competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia often faces obstacles due to limited product packaging that fails to adequately reflect product quality, uniqueness, and brand identity. Packaging is not merely a protective container but also a strategic communication tool that influences consumer perceptions, shapes brand image, and supports market expansion. This community service program was carried out at the Banana Chips MSME “Bu Tini” in Semarang, which previously relied on simple plastic packaging without graphic design, brand logo, or product information. The main objective of this program was to assist the MSME in developing both the design and functional aspects of packaging as a strategic effort to strengthen branding, enhance product value, and improve competitiveness. The methodology applied was community-based and participatory, consisting of field observation, focus group discussions, collaborative design with the business owner, and prototype testing of new packaging. The results demonstrate that the redesigned packaging highlights a stronger visual identity through logos, colors, and slogans, while also ensuring practicality, durability, and compliance with food safety standards. Furthermore, the new packaging improved information clarity regarding composition, expiration date, and producer details, which significantly increased consumer trust in hygiene and quality. From a broader perspective, the activity fostered social transformation by raising awareness among the owner and workers about the importance of branding and professional packaging, developing new skills, and positioning the MSME as a role model for similar businesses in the community. This program implies that packaging development is not solely a visual improvement but a strategic branding instrument that can support MSMEs in achieving sustainability and greater competitiveness in local, regional, and potentially digital markets.